Narrative networks storied approaches in a digital age - Alleyne, Brian (Los Angeles Sage, 2015)
This book responds to the dynamic production and consumption of stories of all kinds in popular and academic cultures. It offers a comprehensive discussion of the underlying philosophical and methodological issues of narrative and personal narrative research as well as applying these to the current digital landscape. The book provides practical guidance on data management and use of software for the narrative researcher. Illustrated with examples from a range of fields and disciplines as well as the author's own work on hacking cultures and cultural activism, this title is a must for anyone wanting to learn about narrative approaches in social research and how to conduct successful narrative research in a digital age.
Introduction -- In the beginning there was the social explorer -- Narrative ways of knowing -- Analysing narrative -- Narrative at work in the world -- Constructing narrative -- Techniques and tools for the narrative researcher.
Includes bibliographical references and index.
Keywords: Narrative inquiry (Research method); Communication and technology